Top-down or bottom-up?: Impacts of giraffe browse and water abstraction on two keystone tree species of the Kgalagadi Transfrontier Park - Shadwell, Eleanor (Department of Biological Sciences, 2017)
In this thesis I determine how an emphasis on tourism may have both a top-down and bottom-up affect on the two most dominant tree species in the southern Kalahari Desert of central southern Africa. Both tree species are considered as keystone species especially along ephemeral rivers. My focus is on the impact of the introduction of an extralimital megaherbivore, Giraffa camelopardalis, (top-down) and anthropogenic water abstraction (bottom-up) on the reproductive output and vegetation structure of Acacia erioloba and Acacia haematoxylon in the Kgalagadi Transfrontier Park. I determine the impact of giraffe on canopy structure and reproductive potential of the two tree species by comparing three zones of giraffe density (high, medium and low) along the Auob River. I do this through a series of transects through the river to determine both giraffe and tree density and also photographed several trees to determine change in canopy width, percentage canopy death and change in the number of flowers and pods between the three zones and between species. My results show a significant negative impact of giraffe browse on canopy structure, specifically for A. haematoxylon. I did not however find any significant differences in recruitment between the different giraffe density zones. However, a noticeable decrease in numbers of flowers and pods in the giraffe browse height of trees (2 - 5 m) between zones suggest that giraffe will have a negative effect on the A. haematoxylon population but not the A. erioloba population in the future. I use stable hydrogen and oxygen isotope ratios to determine the water source for the two tree species. I do this relative to the stable isotope ratio of the water extracted from nearby boreholes. I also determine how close to physiological stress the trees are (using specific leaf area, leaf δ¹³C values, canopy death and midday xylem pressure potentials) both upstream and downstream of active boreholes used for two tourist camps. One camp, Nossob, in the Nossob River is abstracting at a high rate while the other camp, Urikaruus, in the Auob River is abstracting at a lower rate. My results for water isotope ratios show that both A. erioloba and A. haematoxylon are using deep groundwater. My results also show that in the dry season, A. erioloba in the Nossob are losing contact with groundwater and have to rely on some as yet unmeasured water source in the soil profile. This 'stress' is not reflected in canopy dieback as yet. The trees continue to transpire in the dry season suggesting that they are physiologically able to adapt to fluctuations in the water table of between 4.5 - 5.2 m between the wet and dry season by closing their stomata but are prone to drought-induced carbon starvation, specifically for trees in the Nossob. Overall, my results show that the impact of giraffe on vegetation structure is already evident for A. haematoxylon, indicative of future negative effects on reproduction. My research also shows that although current levels of water abstraction are as yet not affecting vegetation structure below the abstraction points, the trees are edging closer to thresholds of water stress that would be exacerbated with drought. These findings are discussed within the context of ecosystem health and management implications for the giraffe population and water use within the Park.